DESIGN AND IMPLEMENTATION OF A HIGH-PRECISION, CONSTANT-CURRENT ELECTRICAL MUSCLE STIMULATOR WITH INTEGRATED SAFETY FEATURES - Hussein, Mohammed Barzan (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2025)
This study presents the development and experimental validation of a high-precision constant-current Electrical Muscle Stimulator (EMS) with integrated safety mechanisms for transcutaneous neurostimulation. To address the main drawback of traditional voltage-source designs—output current variation resulting from changes in skin-electrode impedance—an updated Howland pump configuration is used as a precision voltage-controlled current source (VCCS). The circuit incorporates precisely matched 100Ω resistors and a TLO72 operational amplifier, ensuring output current stability within ±5% for load impedances typical of human tissue (500Ω–2 kΩ). An NE555 timer configured as an astable multivibrator generates adjustable biphasic pulses with a frequency range of 1–6.35 Hz, encompassing the therapeutic bands commonly employed in rehabilitation and pain relief. A key aspect of the design is the incorporation of robust patient safety features—often absent from research-grade stimulators—such as galvanic isolation via a medical-grade output transformer and a series 10µF DC-blocking capacitor. Collectively, these provisions guarantee compliance with the IEC 60601-1 standard for medical electrical equipment. Tests demonstrate reliable delivery of a stable balanced biphasic output current across a range of load conditions. The prototype thus confirms that clinical performance in terms of accuracy and safety can be achieved with inexpensive components, offering a reliable and versatile platform for neuromuscular exploration and future electrotherapeutic applications.